Sample dimensional reading tests for first year high school - Lorenzo, Josefina Valenzuela 1933-
Many teachers in reading encounter difficulties in preparing test questions that aim to measure the reading skills acquired by students. By presenting sample multi-dimensional tests in reading vocabulary and comprehension, this paper specifically aimed at helping reading teachers in constructing questions that measure certain reading skills expected to have been acquired at the secondary freshman level; and to guide reading teachers in instructing and sequencing test questions that will help the learner grasp the insight or theme of a literary piece.